1971
DOI: 10.1042/bj1240581
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of amino groups in proteins and peptides

Abstract: A technique is examined for determining amino groups with 2,4,6-trinitrobenzenesulphonic acid, in which the extinction at 420nm of sulphite complexes of the trinitrophenylated amino groups is measured. The sensitivity of the method is 5-200nmol of amino group. The method is especially suitable for checking the extent of blocking or unblocking of amino groups in proteins and peptides, owing to the short time required for reaction (5min at room temperature). The reaction of the reagent with thiol groups has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(149 citation statements)
references
References 19 publications
3
146
0
Order By: Relevance
“…The free amino groups of ethylenediamine spacers introduced into the PVA molecule were measured by the 2,4,6-trinitrobenzenesulfonic acid (TNBS) method. [21][22][23] One hundred microliters of DMSO containing 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (EDC) (0.27 mg) and N-hydroxysuccinimide (NHS) (0.16 mg) were added to 1 mg of the ADOX-isomers dissolved in 0.1 ml of DMSO, respectively, followed by stirring for 2 h at room temperature. Then, PVA-ethylenediamine (10 mg) dissolved in 0.2 ml DMSO was added to the activated-ADOX-isomers and stirred for 4 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free amino groups of ethylenediamine spacers introduced into the PVA molecule were measured by the 2,4,6-trinitrobenzenesulfonic acid (TNBS) method. [21][22][23] One hundred microliters of DMSO containing 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (EDC) (0.27 mg) and N-hydroxysuccinimide (NHS) (0.16 mg) were added to 1 mg of the ADOX-isomers dissolved in 0.1 ml of DMSO, respectively, followed by stirring for 2 h at room temperature. Then, PVA-ethylenediamine (10 mg) dissolved in 0.2 ml DMSO was added to the activated-ADOX-isomers and stirred for 4 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The number of free amino groups of the PVA-ethylenediamine was estimated by the TNBS method. [21][22][23] One mole of PVA showed the color intensity of 25 mol of free amino group. Free g-carboxylic group of ADOX molecule was activated with an equimolar amount of EDC and NHS, and then reacted with PVA-ethylenediamine.…”
Section: Synthesis Of Aconityl-doxorubicinmentioning
confidence: 99%
“…Therefore, only the fraction of free lysine amino-groups in proteins that were modified with charge-bearing groups was quantified, using trinitrobenzenesulphonic acid titration method (Fields, 1971). We found that approximately 25-35% of all aminogroups accessible for modification was modified with chargebearing groups.…”
Section: Measurement Of Molecular Charge and Weightmentioning
confidence: 97%
“…For example, conventional colorimetric (TNBS, fluorometric) 21,22 and chromatographic characterization (HPLC-SEC, RP-HPLC, gel permeation chromatography) [23][24][25] in combination with light scattering, MALDI-MS 24,[26][27][28] , and capillary electrophoresis 29,30 have been applied for analysis of PEGylated proteins. Specific colorimetric detection of PEG with iodine 31, 32 using Fourier transform infrared (FTIR) or Raman spectroscopy 24 and nuclear magnetic resonance 33, 34 have also been described.…”
Section: Introductionmentioning
confidence: 99%